Design and Build a Website-Based Employee Leave Application Information System (Case Study: Company X): Rancang Bangun Sistem Informasi Pengajuan Cuti Karyawan Berbasis Website (Studi Kasus : Perusahaan X) - Azizah, Khoirun Arining; Utami, Ardhini Warih (Universitas Negeri Surabaya, 2024)
This research aims to design and build a website-based information system for employee leave submission and approval specifically aimed at HCGA admins to make it easier to recap data and reduce the remaining employee leave. In general, it is aimed at managers to facilitate the process of approving leave that has been submitted by employees. As well as making it easier for employees to carry out the flow of applying for leave easily and quickly. Employees can receive this information face-to-face with the HCGA (Human Capital General Officer) admin because it can be accessed anytime and anywhere through the website. Rapid Application Development (RAD) is used as a system development method applied in this study. The steps or stages of this method are requirement planning, user design, construction, and cutover. At the requirement planning stage, interviews, observations and literature studies are carried out. At the user design stage, a prototype is made of diagrams according to the needs of the system. The construction stage is carried out to make a system based on the approved prototype design. Meanwhile, in the cutover stage, testing the website that has been built uses the Blackbox testing method. The test is carried out to ensure that the system that has been built does not have errors that can affect the functionality of the system.